Siyasah Dauliyah Konsep Dasar Komunikasi Diplosmasi Internasional : Sebuah Introspeksi bagi Kebangkitan Umat Islam Dunia - Ismail (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2017)
Dauliyah means the good fortune, kingdom, power, authority. While Siyasah Dauliyah means the power of the Head of State to regulate the state in terms of International relations, territorial problems, nationalities, extradition, prisoners, alienation of political prisoners, expulsion of foreign citizens. In addition, it also deals with the problems of dhimmis, religious differences, mutual reciprocity and one-sided with dhimmi, hudud and qishash Or it can be said that regulate the relationship between these countries (Politics of International Law). Methodology used in this study is Library Studies (Library Research), using secondary data (secondary data) of library materials that have been available in libraries or other places and materials or research resources that can be accessed via the internet such as scientific journals , newspapers, news portals, research results from research institutions and documents.